Light‐Modulated Intermittent Wave Groups in a Diffusively Fed Reactive Gel. Issue 16 (11th March 2016) - Luo, Hainan; Wang, Chenlong; Ren, Lin; Gao, Qingyu; Pan, Changwei; Epstein, Irving R.
Abstract: Inspired by the biological growth that takes place in time‐varying external fields such as light or temperature, we design an open reaction‐diffusion system in order to investigate growth dynamics. The system is composed of the Belousov–Zhabotinsky (BZ) oscillatory reaction coupled with a copolymer gel consisting of NIPAAm and a photosensitive ruthenium catalyst. When subject to a unidirectional flow of the BZ reactants, the system displays groups of chemical waves whose structure depends upon the period and amplitude of illumination. Simulations of a modified six‐variable Oregonator model exhibit all the complex wave groups found in our experiments. Studying this growth structure may aid in understanding the influence of periodic environmental variation on complex growth processes in living systems. Abstract : A copolymer gel consisting of NIPAAm and a photosensitive ruthenium catalyst was coupled with Belousov–Zhabotinsky reactants to obtain a diffusively fed reaction system. External periodic light perturbation induces wave groups analogous to certain developmental patterns such as pinnatisect‐shaped leaves.